1992
DOI: 10.2190/7vw4-ge0d-wrku-q62v
|View full text |Cite
|
Sign up to set email alerts
|

Double Exposure: The Combined Impact of the Home and Work Environments on Psychosomatic Strain in Swedish Women and Men

Abstract: This study investigates the relative distribution of home responsibilities and psychosocial work environment characteristics and their associations with psychosomatic strain in a random sample of the female and male working population of Sweden (N = 12,772). Occupational variables investigated were psychological and physical demands, job control, social support, and job hazards. Home characteristics included measures of household work, number and age of children, and child care resources. A sex-pooled logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 61 publications
6
117
0
2
Order By: Relevance
“…Double exposure was also an important factor in shaping mental health; this was in agreement with previous studies based on Hall's theory 28) . Interesting findings emerged from the written comments of participants.…”
Section: Discussionsupporting
confidence: 91%
“…Double exposure was also an important factor in shaping mental health; this was in agreement with previous studies based on Hall's theory 28) . Interesting findings emerged from the written comments of participants.…”
Section: Discussionsupporting
confidence: 91%
“…Instead of focusing specifically on the crossover or interaction between work and home, the double exposure model suggests that exposure to stress occurs in both the home and work environment, with some exposures unique to each environment, and others common to both. If levels of total exposure (common and unique elements from both environments) are high, the risk for negative health outcomes increases (Hall, 1992;Lundberg et al, 1994). Hall (1992) used this approach to study exposures to stress from work and home and their combined effect on psychosomatic strain and found fundamental gender differences in "…the pattern of exposure to the stresses and the rewards of working and home life" (p. 253), and the relationship of this pattern to strain.…”
Section: The Double Exposure Modelmentioning
confidence: 99%
“…If levels of total exposure (common and unique elements from both environments) are high, the risk for negative health outcomes increases (Hall, 1992;Lundberg et al, 1994). Hall (1992) used this approach to study exposures to stress from work and home and their combined effect on psychosomatic strain and found fundamental gender differences in "…the pattern of exposure to the stresses and the rewards of working and home life" (p. 253), and the relationship of this pattern to strain. In her study of 12,772 working Swedish men and women, the greatest odds for psychosomatic strain was for women who worked more than 20 hours a week, had high home stress (defined as the level of burden from household duties) and low control on the job.…”
Section: The Double Exposure Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[4,29] Numerous studies have shown that being a lone mother is particularly disadvantageous, both economically and in terms of mental health. [30,31] Evidence of high levels of distress among lone mothers is reinforced by findings from Hall's study on lone mothers' experiences in the workforce: [32] lower economic status and lower-quality work led to substantial levels of distress among lone mothers relative to their partnered counterparts.…”
Section: Parenthoodmentioning
confidence: 99%